Impatiens kamrupana (Balsaminaceae): a new species from Assam, India - Borah, Souravjyoti; Sarma, Jatindra; Gogoi, Rajib (Phytotaxa, 2019)
Impatiens kamrupana, a new species from Assam, northeast India is described. The new species is easily distinguished from its allied taxa by its bicoloured, white and purple flowers and sub-bucciniform lower sepal with straight to slightly curved spur.